Consumer Animosity (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This paper provides an inclusivereview of the literatureconcerning the consequences and antecedents of animosity on consumer purchasing intentions. Consumer animosity has attracted a lot of attention in the international marketing and business literature in previous years and was found to have various effects on consumer behavior as a result of a version on the foreign products country of origin. The paper reviews the literature that has been conducted on animosity and focuses on certain limitations that are addressed. Suggestions for future research have been also emphasized in the paper.